Analisis Hukum Terhadap Pemeliharaan (Hak Asuh) Anak Di Bawah Umur Berdasarkan Putusan No.990/Pdt.G/2021/Pa.Mks - Makkah HM; Rina Maryana; K. Qanita AB (Pledoi Law Jurnal, 2024)
ABSTRACT: Children who are left behind by divorce their parents sometimes have to become victims of the divorce because the children do not understand the divorce of their parents at that time, later when they grow up they will understand what conditions happened to their parents. Apart from the issue of divorce itself, other problems also arise as a result of the divorce being granted, such as cases regarding who has more rights in carrying out hadhanah (care) for children. The research results obtained are based on Case Decision Number 990/Pdt.G/2021/PA.Mks, in the case of child maintenance, the Panel of Judges put forward the principle that prioritizes the issue of the right to maintain children, not simply